THE CHALLENGES OF GLOBALIZATION OF MEDIA AND WAYS OF CONFRONTATION - Al-Azawy, Muzafar Mandup (ALBAHITH ALALAMI, 2022)
The successive international changes in the economic, political, cultural and other fields resulted in many phenomena that occupied different levels of interest, and have been followed up, studied and analysed by specialists and researchers especially under the development of the media in the global communication.Even though these phenomena had reflections in the communication domain like development and changes in the mechanism of behaviours between the international communities, they created in the meantime a phenomenon that caused an imbalance in the production, spread and the use of the informations that were supposed to be for fewer than 5 countries whereas it actually it is for more than 180 countries.